THE INFLUENCE OF ORGANIZATIONAL CULTURE ON SERVICE QUALITY IN PDAM MUARA TIRTA GORONTALO CITY - Baruadi, Suci Apriani; Mozin, Sri Yulianty; Isa, Rusli (Universitas Negeri Gorontalo, 2024)
This study aims to determine the influence of organizational culture on service quality in PDAM Muara Tirta Gorontalo City. The research approach used in this study is quantitative, where the sample in this study amounted to 100 employees and customers using a research Â approach and research design. Data collection techniques are carried out by distributing questionnaires to employees and customers. The data analysis technique used is simple regression analysis. Regression analysis test results that show the influence of organizational culture on service quality in PDAM Muara Tirta Gorontalo City. Thus the first hypothesis (H1) can be proved or diterima. The R Square value of 0.4 4 9 in other words that 4 4.9% of the independent variables, namely (X) Organizational Culture contributes to the variable (Y) Service Quality, while the remaining 5 5.1% is in the form of contributions from other variables that are not studied in this study, namely competence, leadership, and work commitment.